(untitled) (CIPEEX, 2025)
Introduction: Prenatal care is essential for monitoring the health of pregnant women and their babies throughout pregnancy and the postpartum period. The Ministry of Health’s Caderno 32 standardizes care, providing guidelines for tests and care. Adherence to the guidelines in Caderno 32 is essential to ensure quality care. Objective: To analyze whether the tests recommended for normal prenatal care are being routinely requested. Methodology: This descriptive study with a quantitative approach analyzed the pattern of low-risk prenatal care in Basic Health Units in Anápolis, divided into the Northwest, Northeast, Southwest, and Southeast areas. The study included all Basic Health Units (UBS) that agreed to participate and used an adapted electronic questionnaire. Data collection was conducted after ethical approval and with the consent of the participants. Results: The sample consisted of 54 primary care health professionals, including doctors and nurses, mostly women with 5 to 10 years of experience and aged between 23 and 65, predominantly in the 30 to 40 age group. The professionals were grouped by region. The analysis revealed that, among physical examinations, Doppler ultrasound was the least performed, while laboratory tests showed greater variation, with vaginal secretion bacterioscopy being the least requested in all regions. Conclusion: Routine low-risk prenatal care in the municipality of Anápolis shows slight discrepancies in relation to the guidelines established by Caderno 32 and the Ministry of Health of the state of Goiás.